Illocutionary Acts in Religious Discourse: The Pragmatics of Nouman Ali Khan’s Speeches - Saiful Akmal; Fitriah Fitriah; Haya Zafirah (Langkawi: Journal of The Association for Arabic and English, 2020)
The present inquiry is designed to investigate the use of illocutionary acts in Nouman Ali Khan’s speeches and to analyse the functions of the types of illocutionary acts from the speeches. The data were analysed by using the textual analysis and open coding from three speeches by Nouman Ali Khan in a seminar titled “When Muslims Works Together” at the Islamic Association of North Texas (IANT). They are classified into some categories based on Searle’s theory. The finding of this study showed that (1) there are four types of illocutionary acts; representatives, directives, commissives, and expressives, (2) the illocutionary type of representatives is the most frequent types of illocutionary act appeared in the speeches, i.e., 306 utterances or 63.22% with five functions; informing, stating, describing, reminding and concluding, (3) then, the second most frequently types of illocutionary act appeared in the speeches was the illocutionary directives, i.e., 144 utterances or 29.75% with five functions; suggesting, commanding, inviting, forbidding and questioning, (4) the illocutionary commissives occurred in 22 utterances or 4.55% with two functions; promising and warning., (5) the illocutionary expressives are found in 12 utterances or 2.48% with two functions; praising and expressing hope or wish. This study implies the need for knowledge distribution of  Searle’s classic speech acts concept within the scope of other contemporary  Muslim preachers.